Acute and Chronic Health Impact of Fine Particulate Matter Constituents - Wang, Fuchao; Liu, Cong (Current pollution reports, 2024)
Purpose of Review Ambient fine particulate matter (PM 2.5 ) is a complex mixture of various toxic constituents. Compared with abundance of studies on PM 2.5 total mass, limited evidence is available on the health effects of PM 2.5 constituents on human health outcomes. The purpose of this review is to summarize recent publications over five years on the short-term and long-term health effects of PM 2.5 constituents on human mortality, morbidity, and subclinical biomarkers. Recent Findings PM 2.5 constituents mainly include organic carbon (OC), black carbon (BC), sulfate (SO 4 2− ), nitrate (NO 3 − ), ammonia (NH 4 + ), and heavy metals, all of which were significantly associated with various mortality and morbidity. Exposure to BC, OC, NO 3 − , SO 4 2− , and NH 4 + mainly affected mortality and morbidity from cardiovascular diseases and respiratory diseases and might influence subclinical markers such as blood pressure and serum cytokines. NO 3 − , OC, and BC were reported to be associated with increased risk of diabetes, cancer, and infant mortality. Summary This review systematically summarized the study evidence on the effects of the constituents of PM 2.5 on population health in recent years. BC, OC, soil dust, NO 3 − , SO 4 2− , and NH 4 + were significantly associated with multisystem health outcomes. We found that the majority of studies were investigating the short-term effects, and mainly focusing on mortality and morbidity endpoints, while there were relatively few literatures on subclinical indicators and other endpoints like adverse birth outcomes. Future studies should be supplemented in this area.